2008
DOI: 10.1002/adma.200702377
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Xylitol‐Based Polymers

Abstract: Synthetic biodegradable polymers have made a considerable impact in various fields of biomedical engineering, such as drug delivery and tissue engineering. The design of synthetic biodegradable polymers for bioengineering purposes is challenging because of the application-specific constraints on the physical properties, including mechanical compliance and degradation rates, and the need for biocompatibility and low cytotoxicity.[1] The monomer selection frequently limits the range of required material properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 25 publications
3
123
2
2
Order By: Relevance
“…Therefore, the larger amount of acid can increase the content of the branched structure, which leads to a decrease of T g . Compared with data in the literature [14], T g s of PXGS 1:1-5% (2.4 °C ) and 1:2-5% (−5.5 °C ) were much lower than those of PXS 1:1 (7.4 °C ) and 1:2 (22.9 °C ) at the same acid/xylitol ratio. In addition, the T g was further decreased on increasing the feeding amount of Boc-L-glutamic acid (Figure 4).…”
Section: Thermal Propertiescontrasting
confidence: 71%
See 2 more Smart Citations
“…Therefore, the larger amount of acid can increase the content of the branched structure, which leads to a decrease of T g . Compared with data in the literature [14], T g s of PXGS 1:1-5% (2.4 °C ) and 1:2-5% (−5.5 °C ) were much lower than those of PXS 1:1 (7.4 °C ) and 1:2 (22.9 °C ) at the same acid/xylitol ratio. In addition, the T g was further decreased on increasing the feeding amount of Boc-L-glutamic acid (Figure 4).…”
Section: Thermal Propertiescontrasting
confidence: 71%
“…It was obvious that the water contact angle of PXS and PXGS was lower than 90°, which indicated that the bioelastomers showed hydrophilicity. The water contact angle of PXS found in this work was higher than that of Langer's results [14]. At the same ratio of acid/xylitol, the contact angle values of PXGS were lower than these of PXS, and further decreased on increasing the content of Boc-L-glutamic acid (Figure 7).…”
Section: Hydrophilicitycontrasting
confidence: 66%
See 1 more Smart Citation
“…The PMS 1 : 1 with a low degree of crosslinking had average UTS of 1.2 AE 0.7 MPa and a Young's modulus of 1.8 AE 0.3 MPa, while for the high crosslinking degree these values increase to 7.0 AE 0.6 MPa and 54.4 AE 3.3 MPa, respectively. While doubling the feed ratio of the sebacic acid monomer, the crosslink density increased 30 and for low degree of crosslinking samples a four-fold enhancement in UTS (4.5 AE 0.7 MPa) and Young's modulus (7.2 AE 0.1 MPa) values were obtained compared with 1 : 1 stoichiometry. Elongation at break of these samples (low crosslinking degree) is also hardly affected by changing stoichiometry to 1 : 2 ratio being reduced by half.…”
Section: Characterization Of Initial Samplesmentioning
confidence: 98%
“…According to previously published methods [7,8,30], PGS and poly(xylitol sebacate) (PXS) can be synthesized in two steps. A pre-polymer was first synthesized by polycondensation of an 1:1 molar ratio of either glycerol or xylitol (purity 99%) mixed with sebacic acid (purity 99%).…”
Section: Synthesismentioning
confidence: 99%